Lung function, hypoxic and hypercapnic ventilatory responses, and respiratory muscle strength in normal subjects taking oral theophylline. Issue 10 (October 1990) - Javaheri, S; Guerra, L
Abstract : Methylxanthines are known to be respiratory stimulants and are thought by some to augment hypercapnic and hypoxic ventilatory drive and improve respiratory muscle strength. Hypoxic and hypercapnic ventilatory responses were measured in 10 normal subjects before, during, and after administration of theophylline for three and a half days. Pulmonary function, carbon dioxide production, and mouth pressures during maximal static inspiratory and expiratory efforts were also measured. The mean (SD) serum theophylline concentration was 13.8 (3.2) mg/l. Lung volumes and flow rates did not change significantly with theophylline. The mean (SD) values for maximum static inspiratory pressure were 152 (27), 161 (25), and 160 (24) cm H2O, respectively before, during, and after theophylline. Neither these values nor peak expiratory pressure measurements were significantly changed. The slopes of the hypercapnic ventilatory responses were 2.9 (0.9), 3.3 (1.2), and 3.3 (1.4) l/min/mm Hg carbon dioxide tension (PCO2) respectively before, during, and after theophylline administration. The respective values for the slopes of the hypoxic response were -1.4 (0.9), -1.3 (0.8), and -1.1 (0.9) l/min/1% oxyhaemoglobin saturation. None of these values changed significantly with theophylline. Theophylline, however, increased carbon dioxide production (200 to 236 ml/min) and alveolar ventilation (4.7 to 5.7 l/min) significantly, with a concomitant fall of end tidal PCO2 (35.5 to 32.9 mm Hg). It is concluded that in man oral theophylline at therapeutic blood concentrations increases carbon dioxide production and ventilation without changing pulmonary function, respiratory muscle strength, or the hypoxic or hypercapnic ventilatory response significantly.